2020
DOI: 10.1177/0963689720908500
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-Derived Extracellular Vesicles in Tissue Regeneration

Abstract: Mesenchymal stem cells (MSCs) are multipotent stem cells that have attracted increasing interest in the field of regenerative medicine. Previously, the differentiation ability of MSCs was believed to be primarily responsible for tissue repair. Recent studies have shown that paracrine mechanisms play an important role in this process. MSCs can secrete soluble molecules and extracellular vesicles (EVs), which mediate paracrine communication. EVs contain large amounts of proteins and nucleic acids, such as mRNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 120 publications
1
40
0
Order By: Relevance
“…In recent years, studies have shown that the role of stem cells in tissue repair is accomplished through the activation of peripheral receptor cells by exosomes secreted by their paracrine mechanism (Tan et al, 2020;Wang et al, 2020;Zhang B. et al, 2020). The exosome molecule is 50-150 nm in diameter, and it mainly contains cytokines, growth factors and other proteins, lipids, coding, or non-coding RNAs similar to the cells of origin, and participates in cell communication, cell migration, vascular regeneration and other processes, which plays an important role in the regulation of cell physiological functions (Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies have shown that the role of stem cells in tissue repair is accomplished through the activation of peripheral receptor cells by exosomes secreted by their paracrine mechanism (Tan et al, 2020;Wang et al, 2020;Zhang B. et al, 2020). The exosome molecule is 50-150 nm in diameter, and it mainly contains cytokines, growth factors and other proteins, lipids, coding, or non-coding RNAs similar to the cells of origin, and participates in cell communication, cell migration, vascular regeneration and other processes, which plays an important role in the regulation of cell physiological functions (Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, EPC-, CPC-, and CBSC-secreted EVs benefit cardiac repair and regeneration following ischemic injury [ 4 , 35 ]. However, EV cargo and biological properties differ depending on physiological condition of their parental cells [ 12 , 13 , 14 ]. Different biological content such as DNAs, RNAs, and proteins are selectively sorted into EVs, while stem/progenitor cells are under physiological conditions or with stress.…”
Section: Discussionmentioning
confidence: 99%
“…EVs including exosomes, 30–100 nm extracellular nano-vesicles, are major regulators for local and remote cell–cell communication and cell signaling induction by transferring material including DNAs, RNAs, proteins, and lipids to recipient cells [ 10 ]. Recent reports show that EV/exosome therapy is an alternative stem cell-free strategy involved in tissue protection and regeneration post-injury [ 11 , 12 , 13 ]. However, EV/exosome quality and production are not static; their activity, components, and function are affected by stem cell origin [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, EVs can promote myocardial regeneration and restore cardiac Most of the literature concerning EVs released by MSCs is isolated from different tissues. That is why we barely mention the topic and for more in depth information we refer to some recent reviews [159,160].…”
Section: Extracellular Vesicles-based Regenerative Medicinementioning
confidence: 99%
“…Due to their lower immunogenicity, easier handling, and having no risk of tumor formation, researchers recently focused on their potential as possible alternatives to stem cells [159,[204][205][206], studying experimental model diseases treated with MSC-EVs. To date, a total of eight clinical trials on the application of EVs for disease treatment were identified [160]. Accordingly, many researchers investigated the role of EVs released by iPSCs in tissue regeneration.…”
Section: Induced Pluripotent Stem Cell Derived Evs In Regenerative Mementioning
confidence: 99%